2018
DOI: 10.1002/celc.201801198
|View full text |Cite
|
Sign up to set email alerts
|

Using an AlCl3/Urea Ionic Liquid Analog Electrolyte for Improving the Lifetime of Aluminum‐Sulfur Batteries

Abstract: Aluminum‐sulfur (Al−S) chemistry is attractive for the development of next‐generation rechargeable battery systems. However, only a few reversible Al−S cells have been reported until now. This paper demonstrates that the use of an AlCl3/urea electrolyte in Al−S cells is a promising approach to improve the cycle life and reach a high discharge voltage plateau of ∼1.6–2.0 V. In contrast to the instability of sulfur in the conventional AlCl3/EMIC electrolyte, sulfur is chemically stable in the AlCl3/urea electrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 26 publications
3
62
0
Order By: Relevance
“…[ 66 ] With a lithium‐ion mediation strategy, reversible Ca‐S cells have been demonstrated recently. [ 20 ] After the success in operating these reversible batteries, mechanistic studies on Mg‐S, [ 67 ] Al‐S, [ 68 ] and Ca‐S [ 20 ] cell systems have been executed. Figure summarizes the electrochemical characteristics of the Mg‐S, Al‐S, and Ca‐S cells in terms of their charge‐discharge behavior and CV performance.…”
Section: Principle and Mechanisms Of Metal–sulfur Chemistriesmentioning
confidence: 99%
“…[ 66 ] With a lithium‐ion mediation strategy, reversible Ca‐S cells have been demonstrated recently. [ 20 ] After the success in operating these reversible batteries, mechanistic studies on Mg‐S, [ 67 ] Al‐S, [ 68 ] and Ca‐S [ 20 ] cell systems have been executed. Figure summarizes the electrochemical characteristics of the Mg‐S, Al‐S, and Ca‐S cells in terms of their charge‐discharge behavior and CV performance.…”
Section: Principle and Mechanisms Of Metal–sulfur Chemistriesmentioning
confidence: 99%
“…The energy storage mechanism for all metal-sulfur batteries follows a conversion type mechanism [13,[150][151][152][153][154]. A simple version of this reaction occurs for lithium, sodium and magnesium [151][152][153][154][155][156][157][158][159][160][161][162][163][164][165][166].…”
Section: Metal-sulfur Batteriesmentioning
confidence: 99%
“…Both Li 2 S and Al 2 S 3 were identified in the discharged cathode. Furthermore, Bian et al reported a record long‐life Al–S battery by using AlCl 3 /urea electrolyte ( Figure ) . Compared with the higher reactivity of sulfur species and the conventional AlCl 3 /EMICl electrolyte, the AlCl 3 /urea electrolyte and sulfur species coexisted stably.…”
Section: Electrolyte Design For Metal–sulfur Batteriesmentioning
confidence: 99%
“…Schematic of an Al–S cell with the electrolyte of AlCl 3 /urea. Reproduced with permission . Copyright 2018, Wiley‐VCH.…”
Section: Electrolyte Design For Metal–sulfur Batteriesmentioning
confidence: 99%